2012
DOI: 10.1167/12.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Compatible and incompatible representations in visual sensory storage

Abstract: Sensory storage shows a short-lived part-report advantage that survives an aftercoming visual noise pattern (Smithson & Mollon, 2006). We tested whether such an advantage survives different types of high-contrast mask. The target was a 3 × 4 array of digits. The mask could be (a) a noise pattern, (b) an array of eights, or (c) an array of random digits. In a preliminary experiment, target and mask were interleaved (at 140 Hz) and target contrast was varied to determine the level at which performance fell to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
13
1
1
Order By: Relevance
“…In the visible face condition, a static face was presented to both eyes, whereas in the invisible face condition, dynamic high-contrast noise replaced the face presented to one eye. This has the disadvantage that we do not know to what extent and how the flashing of the noise patterns influenced our SF results (see Yang and Blake, 2012). We chose suppression noise that was used in several previous studies and found to be very effective (i.e., high-contrast Mondrian patterns; e.g., Tsuchiya and Koch, 2005; Jiang and He, 2006; Jiang et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In the visible face condition, a static face was presented to both eyes, whereas in the invisible face condition, dynamic high-contrast noise replaced the face presented to one eye. This has the disadvantage that we do not know to what extent and how the flashing of the noise patterns influenced our SF results (see Yang and Blake, 2012). We chose suppression noise that was used in several previous studies and found to be very effective (i.e., high-contrast Mondrian patterns; e.g., Tsuchiya and Koch, 2005; Jiang and He, 2006; Jiang et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…When semantic meaning is further associated with emotional arousal, commonly feared, or pleasant stimuli (e.g., a murder scene, erotica) can prioritize attention relative to neutral stimuli (LaBar et al, 2000; Nummenmaa et al, 2006, 2009). Only two other studies to date have examined the competition between visual salience and affective salience within a single complex scene: One study found that, when neutral background pictures were edited to contain a single affectively salient and a single visually salient object, fixations were more likely to be on affectively salient objects (Humphrey et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Affective salience has also been found to increase viewing duration for both pleasant and unpleasant scenes (Lang et al, 1993) and to capture greater initial attention as well as inhibit subsequent disengagement from a stimulus location (Mogg and Bradley, 1999; Fox et al, 2002). In a recent study, when neutral background scenes were edited to contain a single emotionally salient object and a single visually salient object (Humphrey et al, 2012), more fixations were allocated to affectively salient than visually salient objects. Another recent study found tradeoffs between the influence of visual salience and the reward-punishment value of saccade locations, with value overriding visual salience in attracting saccades at latencies over 184 ms (Schutz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we can discover a new figure when we rotate a previously seen image in our mind. However, such discoveries are not “really” new but just new “interpretations.” In two recent publications, we have shown that mental imagery can lead to perceptual learning (Tartaglia et al, 2009, 2012). Observers imagined the central line of a bisection stimulus for thousands of trials.…”
mentioning
confidence: 88%